Time-local stochastic equation of motion for solid ionic electrolytes - A. Rodin; B. A. Olsen; A. Ustyuzhanin; A. Maevskiy (Physical Review Research)
Numerical studies of ionic motion through solid electrolytes commonly involve static nudged-elastic band methods or costly ab initio molecular dynamics. Building on a time-local model of current carrier-electrolyte interaction and incorporating thermal motion, we introduce an approach that is intermediate between the two well-established methodologies by treating the electrolyte as an effective medium that interacts with the mobile particle. Through this coupling, the thermally vibrating electrolyte imparts energy to the charge carriers while also absorbing energy from them due to its own finite elasticity. Using a simple model system, we validate our approach through a series of numerical simulations. Our methodology reproduces both dissipative and diffusive behavior and helps link microscopic system parameters to measurable macroscopic properties.